2023
DOI: 10.1002/ente.202300474
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Simulation, and Experimental Analysis of a Photovoltaic and Biogas Hybrid Renewable Energy System for Electrification of Rural Community

Abstract: This research is a numerical study, with simulation and experimental investigation of a novel photovoltaic and biogas hybrid renewable energy system. PVSYST simulation software is used to evaluate the energy generation of photovoltaic (PV) systems installed at optimum tilt angle and interrow spacing, as well as measure the performance ratio and system losses. The results obtained from simulations show that annual energy production from designed PV system is 16 654.80 kWh year−1 and its annual specific energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…A survey has been conducted in the off-grid region, and it was found that the average household within the region has more than 10 animals. Table 4 provides information on the average manure production of several living things (Habib et al, 2023b).…”
Section: Designing Of Biogas Plantmentioning
confidence: 99%
See 4 more Smart Citations
“…A survey has been conducted in the off-grid region, and it was found that the average household within the region has more than 10 animals. Table 4 provides information on the average manure production of several living things (Habib et al, 2023b).…”
Section: Designing Of Biogas Plantmentioning
confidence: 99%
“…Monocrystalline and polycrystalline silicon PV module cells remain the main photovoltaic technology, with fabrication/production costs of components of about $ 1.50 per watt (Razykov et al, 2011). Habib et al (2023b) presented research on the production of biogas energy, which can be produced from various sources, like an animal and municipal waste. Anaerobic digestion of animal manure reduces environmental pollution and produces comparatively cheap/inexpensive and easily accessible energy for dairy farms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations